Determination of publication performance: Analysis of organizational culture and leadership style mediated by motivation - Abrar Hiswara; Hapzi Ali; Ni Nyoman Sawitri; Zahara Tussoleha Rony (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to identify the factors influencing publication performance at universities in West Java. Research Methodology: The research applies a quantitative descriptive method using both primary and secondary data. Primary data were collected through questionnaires with a 5-point Likert scale, while secondary data came from relevant academic sources such as Scopus, Web of Science, Elsevier, Sinta, and Google Scholar. The sample size was determined using the Hair formula, and data were analyzed using SmartPLS 4.1.0.0 through outer model, inner model, and hypothesis tests. Results: The study found that organizational culture and leadership style each have a positive and significant effect on motivation, while both variables also positively and significantly influence publication performance. Motivation itself was shown to have a positive and significant impact on publication performance. Furthermore, the results indicate that organizational culture and leadership style each exert a positive and significant indirect effect on publication performance through motivation as a mediating variable. Conclusions: Organizational culture, leadership style, and motivation significantly enhance university publication performance in West Java. Limitations: This study is limited to publication performance in higher education institutions in West Java. Contribution: This study aims to identify factors that influence publication performance, with a focus on organizational culture, leadership style, and motivation.